2019
DOI: 10.1590/1807-3107bor-2019.vol33.0090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on gingival inflammation in representative samples of three South American cities

Abstract: Mariel GÓMEZ (c) Ricardo COSTA (a) Andres TOLEDO (c) Fernando SOLANES (b) Hugo ROMANELLI (c) Jorge GAMONAL (b) Rui Vicente OPPERMANN (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(41 reference statements)
4
5
0
1
Order By: Relevance
“…In our study, a higher PI was observed in PerioC-Y-Smk, in all periods evaluated. This finding reinforces the evidence that smokers present worse control of biofilm when compared with non-smokers, as demonstrated in previous clinical studies, 28,29 severity of periodontal disease and the smoking habit, which directly influence the quality of life of these individuals. 5 However, the higher plaque accumulation could be a determinant of the lower periodontal treatment response.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, a higher PI was observed in PerioC-Y-Smk, in all periods evaluated. This finding reinforces the evidence that smokers present worse control of biofilm when compared with non-smokers, as demonstrated in previous clinical studies, 28,29 severity of periodontal disease and the smoking habit, which directly influence the quality of life of these individuals. 5 However, the higher plaque accumulation could be a determinant of the lower periodontal treatment response.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, a higher PI was observed in PerioC‐Y‐Smk, in all periods evaluated. This finding reinforces the evidence that smokers present worse control of biofilm when compared with non‐smokers, as demonstrated in previous clinical studies, 28,29 even after strict professional plaque control. One of the hypotheses for this low compliance in oral hygiene care is the association with low self‐esteem, resulting from masticatory and aesthetic problems related to the severity of periodontal disease and the smoking habit, which directly influence the quality of life of these individuals 5 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study revealed that individuals with more smoking habit exhibit no or mild gingivitis and calculus but their periodontal condition was poor. Similar results were observed in different studies [30][31][32] while results reported by Bregstrome et al are inconsistent with this study, in that study calculus load increased with increasing smoking exposure 33 . Moreover, missing teeth and dental caries frequency in this study shows a positive relation with smoking and results are consistent with other studies [34][35][36][37] .…”
Section: Discussionsupporting
confidence: 64%
“…Los resultados evidenciaron que los pacientes fumadores pesados en comparación con los fumadores ligeros y moderados presentaban menores niveles de inflamación gingival y sangrado a pesar de tener grandes cantidades de placa y cálculos. Se evaluó el riesgo de tener inflamación gingival severa (GI>2) para fumadores ligeros, moderados y pesados (OR=2.27,CI=1.46-3.53; OR=1.62, CI=0.90-2.94; OR= 0.67,CI=0,49-0,92 respectivamente (48).…”
Section: Hábito De Fumarunclassified